2011
DOI: 10.1182/blood-2010-10-300970
|View full text |Cite
|
Sign up to set email alerts
|

Consensus recommendations for risk stratification in multiple myeloma: report of the International Myeloma Workshop Consensus Panel 2

Abstract: A panel of members of the 2009 International Myeloma Workshop developed guidelines for risk stratification in multiple myeloma. The purpose of risk stratification is not to decide time of therapy but to prognosticate. There is general consensus that risk stratification is applicable to newly diagnosed patients; however, some genetic abnormalities characteristic of poor outcome at diagnosis may suggest poor outcome if only detected at the time of relapse. Thus, in good-risk patients, it is necessary to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
232
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(239 citation statements)
references
References 29 publications
2
232
2
3
Order By: Relevance
“…17 There are some reports that 1q21 gains may have clinical significance as a poor-risk feature; however, 1q21 has not yet made its way into routine FISH markers to predict prognosis. 18 This study has focused on the chromosome 1q21 gains in MM patients and analyzed the poor outcomes of newly diagnosed MM patients with 1q21 gains by FISH despite novel agent-based therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 There are some reports that 1q21 gains may have clinical significance as a poor-risk feature; however, 1q21 has not yet made its way into routine FISH markers to predict prognosis. 18 This study has focused on the chromosome 1q21 gains in MM patients and analyzed the poor outcomes of newly diagnosed MM patients with 1q21 gains by FISH despite novel agent-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…18 A long-term analysis of the IFM99 trials for myeloma established that cytogenetic abnormalities 1q21 gains play a major role in defining long-term survival. 19 However, the Mayo Clinic showed that this parameter was not retained in multivariate analyses and that its prognostic value disappeared when combined with other classical biological and genetic prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…4). Discussion MRI pattern of marrow involvement and specific cytogenetic abnormalities have been associated with prognosis in newly diagnosed patients with symptomatic myeloma [4][5][6][7][8][9]. However, there are very limited data in the literature for the correlation between MRI patterns and cytogenetic aberrations in myeloma patients.…”
Section: Mri Patterns and Cytogenetic Abnormalitiesmentioning
confidence: 98%
“…To date, the definition of high risk myeloma is based mainly on stage, according to the International Staging System (ISS) and on cytogenetic abnormalities. The International Myeloma Working Group has recently suggested that the cytogenetically detected chromosomal 13 or 13q deletion, translocation t(4;14) and deletion 17p, and detection by fluorescence in situ hybridization (FISH) of t(4;14), t (14;16), and del17p are considered as poor risk features [6]. Other cytogenetic aberrations, such as the add1q21 and the hypodiploidy have also correlated with poor prognosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The [18][19][20]. Most recently, the International Myeloma Workshop issued a consensus recommendation for high risk stratification of newly diagnosed multiple myeloma to include the above and added that patients in good-risk who show these abnormalities at relapse are considered having a high risk [21].…”
Section: Discussionmentioning
confidence: 99%